Construction of a solution of one integrodifferential equation - Skutar, I.D. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
By using a method proposed by R. Langer, we construct a formal solution of an integral differential equation obtained after the asymptotic integration of one system of linear differential equations with a small parameter of a part of derivatives.